Research Progress on Non-coding RNAs in Cholesteatoma of the Middle Ear - Dongliang Liu; Hang Zhang; Xiulan Ma; Yaodong Dong (Clinical and Experimental Otorhinolaryngology, 2023)
Cholesteatoma of the middle ear is a common disease in otolaryngology that is receiving increasing attention. It is estimated that over five million people around the world have suffered from middle ear cholesteatoma. The annual incidence of middle ear cholesteatoma has been reported to be 9.2 per 100,000 in adults and 3 per 100,000 in children. Without timely discovery and intervention, cholesteatomas can become perilously large and damage intratemporal structures, causing various intracranial and extracranial complications. No practical nonsurgical treatments are currently available. Although multiple hypotheses exist, research directions have consistently focused on cell proliferation, apoptosis, and bone destruction. Non-coding RNAs (ncRNAs), especially microRNAs (miRNAs), long ncRNAs (lncRNAs), and circular RNAs (circRNAs), have recently received increasing attention because of their key roles in gene expression, cell cycle regulation, and the development of many diseases. Although ncRNAs are not involved in protein translation, they are abundant in the genome, with only approximately 2% of genes encoding proteins and the remaining approximately 98% encoding ncRNAs. The purpose of this review is to summarize the current state of knowledge regarding the specific role of ncRNAs in middle ear cholesteatoma.